PENGARUH PENDIDIKAN, KECERDASAN EMOSIONAL DAN KECERDASAN INTELEKTUAL TERHADAP KINERJA PEGAWAI PADA DINAS KESEHATAN KABUPATEN LAHAT - DANANG HADI (Sekolah Tinggi Ilmu Ekonomi (STIE) Serelo Lahat, 2021)
The purpose of this study was to determine and analyze the effect of education on the performance of Lahat District Health Office employees, emotional intelligence on the performance of Lahat District Health Service employees, Intellectual Intelligence on the Lahat District Health Office employees' performance, Education, Emotional Intelligence and Intellectual Intelligence on the performance of Health Service employees. Lahat District. In this study used primary data and secondary data, primary data obtained by distributing questionnaires to 88 respondents who became the sample. The data analysis technique used is Multiple Linear Regression from the SPSS software package, used in hypothesis testing. From the results of data analysis on the variables studied, namely Education, Emotional Intelligence and Intellectual Intelligence, it shows a significant relationship with the performance of the Lahat District Health Office employees.